Zur Übersetzungsäquivalenz deutscher und polnischer Phraseologismen mit Farbbezeichnungen - Płomińska, Małgorzata (Glottodidactica, 2001)
The article is an attempt to lay down equivalents of German and Polish idiomatic phrases with colour names. The search for types of equivalence is founded upon three semantic levels of idioms as well as upon the principle of invariability in the process of translation. In this way the author tries to distinguish three types of equivalence: phraseological, lexical and zero equivalence which is prevalent in case of German and Polish phrases with colour names.